Efficient threshold self-healing key distribution with sponsorization for infrastructureless wireless networks - Han, Song; Tian, Biming; He, M.; Chang, Elizabeth (IEEE, 2009)
Self-healing key distribution schemes are particularly useful when there is no network infrastructure or such infrastructure has been destroyed. A self-healing mechanism can allow group users to recover lost session keys and is therefore quite suitable for establishing group keys over an unreliable network, especially for infrastructureless wireless networks, where broadcast messages loss may occur frequently. An efficient threshold self-healing key distribution scheme with favorable properties is proposed in this paper. The distance between two broadcasts used to recover the lost one is alterable according to network conditions. This alterable property can be used to shorten the length of the broadcast messages. The second property is that any more than threshold-value users can sponsor a new user to join the group for the subsequent sessions without any interaction with the group manager. Furthermore, the storage overhead of the self-healing key distribution at each group user is a polynomial over a finite field, which will not increase with the number of sessions. In addition, if a smaller group of users up to a threshold-value were revoked, the personal keys for non-revoked users can be reused.